Diversity in Criminology and Criminal Justice Studies - Silva, Derek M. D.; Deflem, Mathieu (Emerald Publishing Limited, 2022)
Volume 27 of Sociology of Crime, Law and Deviance discusses a variety of issues of significance to equity, inclusion, and diversity in criminology and criminal justice studies. The research area of crime, criminal justice, and social control has typically devoted attention to diversity in its subject matter much more than in the profession and scholarship itself. By and large, the disparities in the criminal justice system are much better known than the inequities that exist in criminology and among scholars of criminal justice. The authors in this volume demonstrate the theoretical and methodological maturity and diversity in reflexive accounts of criminology and criminal justice in a number of areas, such as and teaching and research in criminology, queer criminology, the intersections of race and gender, indigeneity and decolonization, domestic violence, human rights, mass incarceration, LBGTQI+ rights, and ableism. Presenting a state-of-the-art overview of diversity in criminological and criminal justice methodologies, this volume should be of interest to a wide range of scholars and students in the fields of criminology, sociology, law, justice policy, and criminal justice.
Keywords: Criminology.; Diversity in the workplace.; Social Science -- Criminology.; Crime & criminology.; elektronické knihy; electronic books